Influence of an armrest support on handgrip strength in different arm and shoulder flexion angles in overhead postures - Ochoa Ortiz, Carlos Alberto (2022)
A study was undertaken in which the handgrip strength in three arm positions above the shoulder was measured to compare handgrip strength when arm support is used and when it is not used. Grip forces were generated in pairs of flexion angles, corresponding to shoulder and elbow at 90°–90°, 135°–45° and 160°–20°. Thirty-two participants completed the present study; 23 men and nine women with a median age of 23.1 (SD ±3.6) years. A manual handgrip dynamometer (0–90 kg) and an adjustable angle arm support (AAAS) were used during the data collection. Two-way analysis of variance (ANOVA) for repeated measurements indicates a significant effect of the AAAS factor on the handgrip strength, as well as on the AAAS × angle interaction. However, there is no significant effect of the angle factor on the AAAS × angle interaction.